HUBUNGAN PEMANFAATAN PELAYANAN KESEHATAN IBU HAMIL DENGAN PEMILIHAN FASILITAS PERSALINAN DI INDONESIA - Hadi Ashar; Leny Latifah; Ina Kusrini; Dwi Hapsari Tjandrarini (Faculty of Medicine, Universitas Islam Indonesia, 2019)
Background: Maternal mortality rate (MMR) in Indonesia is still high, 359 per 100,000 born alive. One of the government's efforts to reduce MMR is by providing antenatal care (ANC) service, and holding pregnancy classes (KIH). KIH is a program to increase maternal knowledge and support the making pregnancy safer (MPS) program policy, which is an Obstetric service approach, that every pregnant woman must be assisted by health workers. Objective: The purpose of this study is to determine the relationship between ANC and KIH to the place and birth attendants.Methods: A cross-sectional study, national health indicator survey (SIRKESNAS) 2016, calculation of samples based on the 2010 population census (SP) data. Primary sampling unit (PSU) is a sub-district selected as probability proportional to size (PPS), households that have children aged 0-59 months (Eligible households), samples were selected by simple random sampling of eligible households, as many as 7,313 mothers. The collected variables were ANC, KIH, and the place and birth attendant. Data were analyzed by logistic regression testResults: Logistic regression test results showed that the ANC was positively related to the place of delivery (OR 4,054; p <0.000) and birth attendants (OR 2.659; p <0.000). There was a relationship between KIH and the place of delivery (OR 1,327; p <0.001), and birth attendants (OR 1,718; p <0,000).Conclusion: Mothers who performed at least 4 ANCs, and attended pregnancy classes, were more likely to choose to deliver in health care facilities and deliver with health workers.